2022
DOI: 10.1111/rec.13756
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐ecological evidence highlights that native Prosopis species are better for arid land restoration than non‐native ones

Abstract: The selection of species for restoration projects requires decision-making to be based on scientific evidence as well as input and approval from local communities. To better guide future restoration initiatives, this study assessed the socio-ecological effects of two Prosopis congeners including the native Prosopis cineraria and the non-native P. juliflora (mesquite) in two different sites in Southern Iran. Soil parameters including pH, electrical conductivity, organic carbon, and total nitrogen as well as veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The outcomes of the current study revealed the detrimental impacts of P. velutina on woody species composition and diversity at the Tshidilamolomo and Mabule sites. Several studies have found that the invasion of Prosopis species has reduced native plant richness and density [ 32 , 40 , 41 , 42 , 43 ]. This suggests that the vigorous and rapid growth of this invasive species, which has reached a large proportional representation, is accountable for the strong impact on native woody plant species along the Molopo River.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the current study revealed the detrimental impacts of P. velutina on woody species composition and diversity at the Tshidilamolomo and Mabule sites. Several studies have found that the invasion of Prosopis species has reduced native plant richness and density [ 32 , 40 , 41 , 42 , 43 ]. This suggests that the vigorous and rapid growth of this invasive species, which has reached a large proportional representation, is accountable for the strong impact on native woody plant species along the Molopo River.…”
Section: Discussionmentioning
confidence: 99%
“…Structured questionnaires were used to collect data through interviews with key informants and a household survey (Shiferaw et al, 2022) between June and July 2020 to assess the perceptions of thirty family farmers (Santos et al, 2020;Sharifian et al, 2022) aged between 18 and 65. The semi-structured forms were applied face-to-face, purposive, targeted, and non-probabilistic.…”
Section: Data Collectionmentioning
confidence: 99%
“…Future restoration initiatives require scientific evidence as well as input and approval from local communities. This was presented in the fifth article entitled “Socio‐ecological evidence highlights that native Prosopis species are better for arid land restoration than non‐native ones” (Sharifian et al 2022). The results of the study showed that areas with native P. cineraria had higher native vegetation cover, density, and diversity as compared to sites with the non‐native P. juliflora .…”
mentioning
confidence: 99%